Gastroprotective mechanism of Bauhinia thonningii Schum - Abdelwahab, S.I.; Taha, M.M.E.; Abdulla, M.A.; Nordin, N.; Hadi, A.H.A.; Mohan, S.; Jayapalan, J.J.; Hashim, Onn Haji (2013)
Ethnopharmacological relevance: Bauhinia thonningii Schum. (Cesalpiniaceae) is locally known as Tambarib and used to treat various diseases including gastric ulcer. Aim of the study: The current study aims to evaluate the gastroprotecive mechanism(s) of methanolic (MEBT) and chloroform (CEBT) extracts of Bauhinia thonningii leaves on ethanol-induced gastric ulceration. Materials and methods: Gastric acidity, quantification and histochemistry of mucus, gross and microscopic examination, nitric oxide, lipid peroxidation, 2D gel electrophoresis, mass spectroscopy and biochemical tests were utilized to assess the mechanism(s) underlying the gastroprotective effects of MEBT and CEBT. Effect of these extracts into lipopolysaccharide/interferon-gamma stimulated rodent cells were done in vitro. In vitro and in vivo toxicity studies were also conducted. Antioxidant activities of MEBT and CEBT were examined using DPPH, FRAP and ORAC assays. Phytochemical analyses of MEBT and CEBT were conducted using chemical and spectroscopic methods. Results: Gross and histological features confirmed the anti-ulcerogenic properties of Bauhinia thonningii. Gastroprotective mechanism of MEBT was observed to be mediated through the modulation of PAS-reactive substances, MDA and proteomics biomarkers (creatine kinase, malate dehydrogenase, ATP synthase, actin and thioredoxin). MEBT and CEBT showed no significant in vitro and in vivo effects on nitric oxide. Methanolic extract (MEBT) showed superior gastroprotective effects, polyphenolic content and antioxidant activities compared to CEBT. The plant extracts showed no in vitro or in vivo toxicity. Conclusion: It could be concluded that MEBT possesses anti-ulcer activity, which could be attributed to the inhibition of ethanol-induced oxidative damage and the intervention in proteomic pathways but not the nitric oxide pathway. (C) 2013 Elsevier Ireland Ltd. All rights reserved.